Three-dimensional Reconstruction of the Microstructure of Human Acellular Nerve Allograft - Zhu, Shuang (Sci Rep, 2016)
The exact inner 3D microstructure of the human peripheral nerve has been a mystery for decades. Therefore, it has been difficult to solve several problems regarding peripheral nerve injury and repair. We used high-resolution X-ray computed microtomography (microCT) to scan a freeze-dried human acellular nerve allograft (hANA). The microCT images were then used to reconstruct a 3D digital model, which was used to print a 3D resin model of the nerve graft. The 3D digital model of the hANA allowed visualization of all planes. The magnified 3D resin model clearly showed the nerve bundles and basement membrane tubes of the hANA. Scanning electron microscopy (SEM) was used to analyse the microstructure of the hANA. Compared to the SEM images, the microCT image clearly demonstrated the microstructure of the hANA cross section at a resolution of up to 1.2 μm. The 3D digital model of the hANA facilitates a clear and easy understanding of peripheral nerve microstructure. Furthermore, the enlarged 3D resin model duplicates the unique inner structure of each individual hANA. This is a crucial step towards achieving 3D printing of a hANA or nerve that can be used as a nerve graft.